The Affecting Factors Occurring of Worms in Roof Tile and Bricks Craftsmen in Boyolali - hayani, Nur; Wijayanti, Yuni; Indriyanti, Dyah Rini (Public Health Perspective Journal, 2019)
Worms is a worm infestation of one or more intestinal parasites consisting of intestinal nematodes class. Including transmission through soil or worm species commonly called the Soil Transmitted Helminths (STH) are Ascaris lumbricoides, Trichuris trichuira, Ancylostoma duodenale and Necator americanus. The purpose of this study analyzes the factors that influence the incidence of worm craftsman tiles and bricks in the Village Karanggeneng Boyolali. This research is quantitative, with cross sectional approach. These samples included 88 respondents obtained by simple random sampling technique. Data collection techniques were interviews, observation (observation) and laboratory testing. Analysis of the data in this study using Fisher's Exact test and Multiple Logistic Regression Test. Results of the study found no effect on knowledge variable (p = 0.007), handwashing (p = 0.003), latrine ownership (p = 0.001) on the incidence of intestinal worms in the village Karanggeneng Boyolali. The most influential variable in this study is the latrine ownership variable with OR = 0.406.